Human-Mediated World : Understanding Jatropha Development In Indonesia - Fatimah, Yuti A (Departement of Communication and Community Development, 2014)
This paper uses Actor-Network Theory (ANT) to understand the relation between farmers and nature by seeing how this shapes their participation in agricultural initiatives. Using Jatropha development in indonesia as focus, this paper show that actantsâ relation with nature is mediated through different. Sometimes conflicting, paths. In building the argument, this paper use a historical narrative started from Jatropha research in the laboratory in 2002 up to foreign investment after 2008. This paper identifies three period of Jatropha development in Indonesia in which its classification are based on its actors. Additionally, this paper identifies two type of substituation called function-oriented and actant-oriented determining the network durability. Â© 2014 Journal of Rural Indonesia [JoRI] IPB. All rights reserved.Keywords:Â actant, durability, function, Jatropha, natureReceived: 20th October 2014; Accepted: 15th November 2014[How to Cite: Fatimah, Y. (2014). Human-Mediated World : Understanding Jatropha Development In Indonesia.Â Journal Of Rural Indonesia, 2(1), 31-48. Retrieved fromÂ http://ejournal.skpm.ipb.ac.id/index.php/ruralindonesia/article/view/292]